Cardiorenal outcomes with dapagliflozin by baseline glucose‐lowering agents: Post hoc analyses from DECLARE‐TIMI 58. Issue 1 (22nd September 2020) - Cahn, Avivit; Wiviott, Stephen D.; Mosenzon, Ofri; Murphy, Sabina A.; Goodrich, Erica L.; Yanuv, Ilan; Rozenberg, Aliza; Wilding, John P. H.; Leiter, Lawrence A.; Bhatt, Deepak L.; McGuire, Darren K.; Litwak, Leon; et al.
Abstract: Aim: To assess the associations between baseline glucose‐lowering agents (GLAs) and cardiorenal outcomes with dapagliflozin versus placebo in the DECLARE‐TIMI 58 study. Materials and methods: DECLARE‐TIMI 58 assessed the cardiorenal outcomes of dapagliflozin versus placebo in patients with type 2 diabetes. This post hoc analysis elaborates the efficacy and safety outcomes by baseline GLA for treatment effect and GLA‐based treatment interaction. Results: At baseline, 14 068 patients (82.0%) used metformin, 7322 (42.7%) sulphonylureas, 2888 (16.8%) dipeptidyl peptidase‐4 inhibitors, 750 (4.4%) glucagon‐like peptide‐1 receptor agonists (GLP‐1 RAs) and 7013 (40.9%) insulin. Dapagliflozin reduced the composite of cardiovascular death (CVD) and hospitalization for heart failure (HHF) versus placebo regardless of baseline GLA, with greater benefit in the small group of patients with baseline use of GLP‐1 RAs (HR [95% CI] 0.37 [0.18, 0.78] vs. 0.86 [0.75, 0.98] in GLP‐1 RA users vs. non‐users, P interaction = .03). The overall HR for major adverse cardiovascular events (CVD, myocardial infarction or ischaemic stroke) was 0.93 (95% CI 0.84, 1.03) with dapagliflozin versus placebo, with no interaction by baseline GLA ( P interaction > .05). The renal‐specific outcome was reduced with dapagliflozin versus placebo in the overall cohort (HR [95%CI] 0.53[0.43‐0.66]), with no interaction by baseline GLA ( P interaction > .05). All of these outcomes were similar in those with versus those without baseline metformin use. Conclusions: The effects of dapagliflozin on cardiorenal outcomes were generally consistent regardless of baseline GLA, with consistent benefits regardless of baseline metformin use. The potential clinical benefit of combining sodium‐glucose co‐transporter‐2 inhibitors with GLP‐1 RAs, given some evidence of cardiovascular risk reduction with both classes, should be explored further.